Constitutional law and freedom of expression: a critique of the Constitution of the public sphere in legal discourse and practice with special reference to 20th century American law and jurisprudence - Douzinas, Constantinos (1983)
Freedom of expression has been postulated in the American legal system as a constitutional right and the Federal Judiciary has undertaken to enforce it against legislative enactments that abridge it. Thus, the various liberal and democratic justifications for the free exchange of ideas, opinions and information have been moulded in legal theory and practice with the theory of constitutionalism. Constitutionalism is analysed as the amalgam of the theories of natural law, legal positivism and popular sovereignty. In the 19th century the natural law element predominated and freedom was identified with property rights. But after the New Deal, the democratic element and political freedom asserted a central position in constitutional discourse. Constitutional theory, however, remained within a paradigm dominated by concepts of the classical political philosophy: power is presented as a unitary essence, law as a unified and coherent body of rules and legitimation as a normative characteristic of the sociopolitical order, while the Constitution represents the unity of these elements. The constitutional mode of discourse built around these concepts, seeks to emphasize the legal and social continuity guaranteed by the Constitution and the Supreme Court but is a poor description of the mass democratic- welfare state. Power should be examined as relational, law as a social process politically determined and contradictory and legitimation as a complex and contested characteristic not exclusively normative. American law and jurisprudence on freedom of expression are then examined. The cases are analysed as the political claims of groups and individuals to enter the public sphere; judicial intervention is one of the means through which the latter is constituted. Issues, ideas, individuals and organisations claim participation in it and through their officially sanctioned admission/exclusion the parameters of public discourse are continuously contested and differentially demarcated in each historical moment. Four periods of free speech adjudication are distinguished, each of which presents thematic and doctrinal similarities. The "bad tendency" of speech doctrine was utilised in the first quarter of the century against socialists, pacifists and syndicalists. In the 30s and 40s the contextual characteristics of expression became the subject of regulation and the legal persecution of political dissenters became relaxed. But in the 50s and 60s an attempt to purge the public sphere from radical or reformist ideas and people was undertaken, which was endorsed by the Supreme Court by means of the "balancing" doctrine. Finally, in the 60s and 70s the federal judiciary distinguished among the various methods of protest through a number of particularistic approaches and while it did not recognise a full right to protest publicly, it prevented an outright legal repression of public political dissent